Occupational science for occupational therapy - Pierce, Doris E., ....- (Thorofare (N.J.) : Slack, 2014)
Occupational Science for Occupational Therapy shows how different types of occupational science research support occupational therapy. The book is research based and moves firmly away from presenting theories and models that are unsupported by research within the field. The book regards occupational therapy as actively involved in producing a science highly responsive to its knowledge needs, instead of as a profession that consumes and applies research that is produced within other disciplines and for other purposes
Includes bibliographical references and index.
Keywords: Ergotherapie -- Onderzoek; Occupational Therapy